Entrepreneurs talent, temperament, opportunity and mindset - Thompson, John (Professor of entrepreneurship); Bolton, Bill (Bill K.) (Abingdon, Oxon New York, NY Routledge, 2024)
"What does it take to be - or to become - a successful entrepreneur? Are there specific personality types that are best suited to entrepreneurship? And can these types, or rather the attributes that combine to forge them, be learned or acquired? In this book, John Thompson answers these questions - and many more - to let the reader see through the eyes of the entrepreneur. Entrepreneurs: Talent, Temperament, Opportunity and Mindset introduces the world of entrepreneurship from a person-centred perspective. Part I builds an understanding of the entrepreneur as a person based on the key factors of talent and temperament - a unique framework for understanding and exploiting entrepreneurial opportunities. Part I also explores the entrepreneurial mindset and how it can be honed and strengthened. The process of starting and growing a business, is then described in detail Part II, which also examines entrepreneurship in the context of opportunity and strategy. Part III introduces the infrastructure and environment in which the entrepreneur has to operate and tells the stories of famous entrepreneurs through dozens of case vignettes, including classic figures such as Henry Ford, through to social entrepreneurs and even anti-social entrepreneurs such as Al Capone! This insightful, empirically-based take on the entrepreneur, provides students with an accessible and original way into entrepreneurship. Whatever their background, students at all levels will value the author's accessible writing style and invaluable insights"--
Bill Bolton appeared as the first named author on earlier editions.
Includes bibliographical references and index.
Keywords: Businesspeople; Entrepreneurship; Success in business